Emergence and outcomes of the SARS-CoV-2 ‘Marseille-4’ variant - Fournier, Pierre-Edouard; Colson, Philippe; Levasseur, Anthony; Devaux, Christian A.; Gautret, Philippe; Bedotto, Marielle; Delerce, Jeremy; Brechard, Ludivine; Pinault, Lucile; Lagier, Jean-Christophe; Fenollar, Florence; Raoult, Didier (International journal of infectious diseases, 2021)
•The severe acute respiratory syndrome (SARS-CoV-2) Marseille-4 variant caused an epidemic that started in August and is still ongoing.•This variant harbours 13 hallmark mutations, including one in the spike receptor binding domain.•The variant predominated in Marseille from September 2020 and caused a re-infection in 11 patients.•Hypoxemia was more frequent than with clade 20A strains that circulated before May 2020.•The sudden appearance of Marseille-4 points towards an animal reservoir, possibly mink. In Marseille, France, following a first severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak in March–May 2020, a second epidemic phase occurred from June, involving 10 new variants. The Marseille-4 variant caused an epidemic that started in August and is still ongoing. The 1038 SARS-CoV-2 whole genome sequences obtained in our laboratory by next-generation sequencing with Illumina technology were analysed using Nextclade and nextstrain/ncov pipelines and IQ-TREE. A Marseille-4-specific qPCR assay was implemented. Demographic and clinical features were compared between patients with the Marseille-4 variant and those with earlier strains. Marseille-4 harbours 13 hallmark mutations. One leads to an S477N substitution in the receptor binding domain of the spike protein targeted by current vaccines. Using a specific qPCR, it was observed that Marseille-4 caused 12–100% of SARS-CoV-2 infections in Marseille from September 2020, being involved in 2106 diagnoses. This variant was more frequently associated with hypoxemia than were clade 20A strains before May 2020. It caused a re-infection in 11 patients diagnosed with different SARS-CoV-2 strains before June 2020, suggesting either short-term protective immunity or a lack of cross-immunity. Marseille-4 should be considered as a major SARS-CoV-2 variant. Its sudden appearance points towards an animal reservoir, possibly mink. The protective role of past exposure and current vaccines against this variant should be evaluated.